2014
DOI: 10.1016/j.memsci.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Self-organized isoporous membranes with tailored pore sizes

Abstract: Membrane formation via the combination of self-assembly and the non-solvent induced phase separation (NIPS) process of diblock copolymers is investigated. Several polystyrene-blockpoly(4-vinylpyridine) (PS-b-P4VP) diblock copolymers with different molecular weights and weight percentages of both blocks are tested under different parameters, leading to membrane surfaces with uniform pores of approximately 20-70 nm diameter. The average pore diameter is proved to be adjustable by changing the total molar mass of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
192
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(195 citation statements)
references
References 46 publications
0
192
0
3
Order By: Relevance
“…[14][15][16] We have shown previously that this technique can be applied to produce nanoporous membranes using the amphiphilic BCPs (PS-b-PEO and PS-b-P4VP). 12.14 Several research groups also demonstrated that this method is viable to produce nanoporous asymmetric BCP membranes However, all the membranes were produced from amphiphilic block copolymers, which contain at least one hydrophobic and one or more hydrophilic segment.…”
mentioning
confidence: 99%
“…[14][15][16] We have shown previously that this technique can be applied to produce nanoporous membranes using the amphiphilic BCPs (PS-b-PEO and PS-b-P4VP). 12.14 Several research groups also demonstrated that this method is viable to produce nanoporous asymmetric BCP membranes However, all the membranes were produced from amphiphilic block copolymers, which contain at least one hydrophobic and one or more hydrophilic segment.…”
mentioning
confidence: 99%
“…Using only one or two layers of polyelectrolyte, they were able to separate mixtures, through diffusion of water, of anionic and cationic dyes (Figure 5c,d), mixtures of differently sized molecules with similar charges, and mixtures of differently sized and charged proteins. 18 Especially of interest was the way that they were able to monitor the membrane pressure using a low-cost sensor (Figure 5a,b) -this became the inspiration for the system design discussed later. Approaching smaller size ranges, the Martin group has performed extraordinary separations using track-etched membranes with 30nm pores into which either gold or silver was electroplated onto the interior pore wall.…”
Section: Membrane Functionalization -Track-etched Membranesmentioning
confidence: 99%
“…At this point, the plan for layer-by-layer deposition was clear -with the low molecular weight PSS and protonated PEI using a base layer of PAA (Scheme 1), the assembly would be studied at different pH levels and characterized using pressure and SEM data. P4VP membranes have shown, 18 it is not possible to derive the pore diameter from a single pressure measurement accurately. This is most likely due to a reasonable number of dead-end pores, combined with some amount of hydrophobic P4VP polymer present in the middle of the pore rather than around the edge.…”
Section: Layer By Layer Deposition -Pressure Data and Analysismentioning
confidence: 99%
“…3). 56,57 The SNIPS process begins by casting a thin film of a block polymer solution on a substrate followed by a period of controlled solvent evaporation. The evaporation of solvent generates an increased polymer concentration at the solution-air interface, which causes the block polymer to form into ordered nanostructures across the top surface of the film.…”
Section: Introductionmentioning
confidence: 99%
“…For sizeselective filtration membranes, a major research objective has recently centered about tuning the membrane pore size through molecular engineering. 57,79 In this regard, fabricating membranes with smaller pore features has been identified as a critical direction of research for extending the applicable range of block polymer membrane devices into the nanofiltration and reverse osmosis regimes useful for desalination. To date, most block polymer membranes have been prepared with pore diameters in the range of 10 to 50 nm.…”
Section: Introductionmentioning
confidence: 99%